La intervención de terceros Estados ante la Corte Internacional de Justicia: identificando criterios jurisprudenciales para la aceptación o denegación de las solicitudes - Roca Calderón, Josselyn (2021)
There are three possible types of intervention by third States in the disputes before the International Court of Justice. Intervention for the interest of a legal nature and intervention for the construction of a convention are stipulated in the ICJ Statute, but intervention by necessity of consent of an indispensable party has been established in the jurisprudence of the aforementioned court. Within this article each type will be detailed, as well as the guidelines and/or criteria established by the ICJ itself, which have provided content to the concepts established in its provisions, either in the Statute or in its Regulations. For these purposes, their jurisprudence will be analyzed in cases with requests for intervention to identify common denominators in their pronouncements.